(untitled) (Eurasian Journal of Philology Science and Education, 2018)
The article is devoted to the study of the work of famous Kazakh writer Abish Kekilbayev. The main object of research is his stories «Dariia hanshanyn tarihy», «Kui», and the novels «Anyzdyn aqyry», «Urker», and «Еlen-alan». Features of artistic thinking, style and skill of the writer are revealed on the basis of analysis of these works. He evaluates the system of characters, describes their souls and hidden motives of actions in his works. The main attention is paid to understanding the ideological and thematic content of stories and novels of A. Kekilbayev. The issues of historical and artistic truth, cultural and folklore traditions, the continuity of literature are explained in the article. Moreover, the article deals with the innovation in the works of A. Kekilbayev and the Kazakh traditions that in his works.